A materialidade do estado: a relação da movimentação de recursos públicos com a acumulação capitalista de riqueza - Wieland Silberschneider (2014)
This thesis aims to demonstrate how the State is inserted within the capitals valorization process by moving part of the surplus generated under market relations, through budgetary and monetary institutional arrangement, appropriating it through compulsory contributions, and redirecting and redistributing it in the form of state income transfers and collective consumption goods, which recompose labor's and capital's income. The approach is based on the critical analysis of Nico Poulantzas as well of the strategic-relational approach's (and its affiliation to the Theory of Regulation) interpretation of the relational nature of the State, pointing their epistemological retrenchment from the Marxist point of view. In this perspective, the analysis discusses how income's moving by the State deals with the wealth accumulation, by means of an institutional materiality, which historically was forged as State to enable the state capacities, and it is headed by a strategic selectivity, which determines the conflicts of interest and therefore the material condensation under the principle of governmental actions value of use disconnection.The thesis also describes the evolution of the capitalist state's materiality, performing the historical evolution of income moving by States and of the budgetary arrangement since nineteenth century, and analyzing, from public income and expenditure data, the changing patterns of the materiality in U.S. and UK since the early twentieth century, as well as in a set of selected countries of the Organization for Economic Cooperation and Development - OECD over the past three decades.